EVALUATION OF ANTIULCEROGENIC ACTIVITY OF METHANOL EXTRACTS OF BRASSICA OLERACEA VAR. CAPITATA RUBRA ON ALBINO RAT GASTRIC ULCERATION - K, SUDHARAMESHWARI; M, Ayshwarya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To investigate the antiulcerogenic activity of methanolic extract of Brassica var. capitata rubra in albino rats. Methods: To evaluate the antiulcer activity by pyloric ligation models experimentally induced gastric ulcer by ranitidine (10 mg/kg) subcutaneously. The parameters taken to assess antiulcer activity were free acidity, total acidity, volume of gastric juice, PH, ulcer score, and ulcer index. Results: The methanolic extract of Brassica oleracea var. capitata rubra in the dose of 0.50 mg/kg produced significant antiulcer activity. The control animals had ulcers and hemorrhagic streaks, whereas in animals administered with extracts of B. oleracea there was a significant reduction in ulcer index (pË‚0.05). Conclusion: This study concluded that methanol extract of B. oleracea var. capitata has healing property of gastric ulcers in albino rats. Keywords: Brassica, Methanol extract, Antiulcer activity, Pyloric ligation model.